Mental health among otolaryngology resident and attending physicians during the COVID‐19 pandemic: National study. Issue 7 (4th June 2020) - Civantos, Alyssa M.; Byrnes, Yasmeen; Chang, Changgee; Prasad, Aman; Chorath, Kevin; Poonia, Seerat K.; Jenks, Carolyn M.; Bur, Andrés M.; Thakkar, Punam; Graboyes, Evan M.; Seth, Rahul; Trosman, Samuel; et al.
Abstract: Background: Otolaryngologists are among the highest risk for COVID‐19 exposure. Methods: This is a cross‐sectional, survey‐based, national study evaluating academic otolaryngologists. Burnout, anxiety, distress, and depression were assessed by the single‐item Mini‐Z Burnout Assessment, 7‐item Generalized Anxiety Disorder Scale, 15‐item Impact of Event Scale, and 2‐item Patient Health Questionnaire, respectively. Results: A total of 349 physicians completed the survey. Of them, 165 (47.3%) were residents and 212 (60.7%) were males. Anxiety, distress, burnout, and depression were reported in 167 (47.9%), 210 (60.2%), 76 (21.8%), and 37 (10.6%) physicians, respectively. Attendings had decreased burnout relative to residents (odds ratio [OR] 0.28, confidence interval [CI] [0.11‐0.68]; P = .005). Females had increased burnout (OR 1.93, CI [1.12.‐3.32]; P = .018), anxiety (OR 2.53, CI [1.59‐4.02]; P < .005), and distress (OR 2.68, CI [1.64‐4.37]; P < .005). Physicians in states with greater than 20 000 positive cases had increased distress (OR 2.01, CI [1.22‐3.31]; P = .006). Conclusion: During the COVID‐19 pandemic, the prevalence of burnout, anxiety, and distress is high among academic otolaryngologists.